ARTISTIC SECRETS OF NURALI KABUL - A.M.Tolipova (Scholar Express Journal, 2022)
The article discusses the history of studying the work of the talented writer Nurali Kabul, some aspects of the writer's artistic skills. In modern literary criticism, the scientific works of scientists who conducted research on the writer's work are partially evaluated. What aspect of the writer's work was given more attention and the role of the writer in our literature is emphasized. Through the analysis of Nurali Gabul's story "The Court", the author expresses his thoughts about the author's artistic courage, the structure of the work, plot and composition
Keywords: Writer; story; image; fiction